Rancang Bangun Sistem Informasi Akuntansi pada Puskesmas Teluk Latak Bengkalis Berbasis Web - Abdillah, Moh Ghufron Eric; Syuhada, Nelly; Putri, Rikha Febriana; Yanti , Vivi Putri; Rahmayani, Mentari Tri Indah (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
An information system is defined as a combination of interconnected elements to collect, process, store and disseminate information required in a particular business or organizational context. This research focuses on designing an accounting information system at the Teluk Latak Community Health Center to improve the efficiency of health services. The research method uses the System Development Life Cycle (SDLC) with the stages of planning, analysis, design, implementation, testing and maintenance. The research results include software requirements analysis, system design using use case diagrams and activity diagrams, as well as testing system features. This web-based system helps improve patient registration, administrative processes, and non-cash payments. The conclusion emphasizes the importance of information systems in optimizing health service management at the Teluk Latak Bengkalis Health Center.